Board of Commissioners in Corporate Governance, Firm Performance, and Ownership Structure - Utama, Cynthia A.; Utama, Sidharta (Universitas Prasetiya Mulya, 2019)
The purpose of this study is to investigate: firstly, the two-way causality between firms performance and the size of BOC; secondly, the non-linear effect of board size on the firms’ performance; thirdly, the direct and moderating effects of the ownership structure on the influence of firm performance on board size. Using the ROA as a measure of firm performance, we find that there is a simultaneous relationship between firm performance and the size of BOC: the size of the board has an inverted U-shaped effect on firm performance while firms performance has a negative influence on board size. We find that the size of the board of commissioners increases firm performance up to a certain level, but a very large board reduces firm performance. We find marginal evidence that ownership structure has a moderating effect on the impact of firm performance on board size. We document that the negative effect of performance on board size dissipates as ownership right increases. The negative effect of performance on board size marginally strengthens. Thus, our study contributes to the literature by finding that the negative influence of firm performance and board primarily occurs on firms that are subject to high incentive expropriation by controlling shareholders.